1990
DOI: 10.1073/pnas.87.12.4665
|View full text |Cite
|
Sign up to set email alerts
|

A DNA replication enhancer in Saccharomyces cerevisiae.

Abstract: We have dissected the autonomously replicating sequence ARS121 using site-directed in vitro mutagenesis. Three domains important for origin function were identified; one of these is essential and contains an 11-base-pair sequence resembling the canonical ARS core consensus; the second region, deletion of which affects the efficiency of the origin, is located 3' to the T-rich strand of the essential sequence and encompasses several elements with near matches to the ARS core consensus; the third region, containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
82
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 53 publications
0
82
0
Order By: Relevance
“…Therefore, the direction of the Abf1p site was not important for silencing by HMR-EЉ. Along this line, it is noteworthy that the orientation of the Abf1p site in an ARS is also not important for its function as a replication origin (38).…”
Section: Hmr-eј Versus Hmr-e)mentioning
confidence: 62%
“…Therefore, the direction of the Abf1p site was not important for silencing by HMR-EЉ. Along this line, it is noteworthy that the orientation of the Abf1p site in an ARS is also not important for its function as a replication origin (38).…”
Section: Hmr-eј Versus Hmr-e)mentioning
confidence: 62%
“…Interestingly, two ARS-binding proteins, ABF 1 (Diffley and Stillman 1988), identified by its affinity to ARS1, and OBF1 (Eisenberg et al 1988), identified by its affinity to ARS121, which were first thought to be different proteins based on their affinities to apparently unrelated sequences, turned out to be the same protein with broad binding specificity (Biswas and Biswas 1990). This finding suggests that if ABF1-OBF1 plays the role of an enhancer of DNA replication (Walker et al 1990), it does so by acting at a large number of ARSs.…”
mentioning
confidence: 78%
“…OBF1 (19,20), identified by its affinity to ARS121, has a DNAbinding specificity similar to that of ABF1, suggesting that these two ARS-binding proteins may be the same (S. Eisenberg, personal communications). Analysis of the OBF1-binding site in ARS121 indicates that this site acts as an enhancer of DNA replication in such a way that stimulation of origin function can be provided by a synthetic OBF1-binding site independent of its orientation or distance 5' from the ARS consensus sequence (71). The role of ABF1 or OBF1 in DNA replication is unclear, since deletion of its binding sites in a number of ARSs causes only a small decrease in plasmid stability (35,59,72).…”
mentioning
confidence: 99%